Barzilai-Borwein Gradient Algorithm Based Alternating Minimization for Single User Millimeter Wave Systems - Mulla, Mustafa; Ulusoy, Ali Hakan; Rizaner, Ahmet; Amca, Hasan (IEEE wireless communications letters, 2020)
In this letter, we investigated the achievable spectral efficiency and complexity of a single-user millimeter wave massive multiple-input-multiple-output system with hybrid analog/digital transceiver architecture. We then proposed a new low-complexity alternating minimization algorithm based on the Barzilai-Borwein gradient algorithm to maximize the spectral efficiency. Accordingly, in order to minimize the Euclidean distance between hybrid precoders and the optimal precoder (fully digital precoder), optimization of analog and digital precoders (or decoders) are presented. Simulation results show that in spite of its lower computational complexity the proposed method can achieve almost the same spectral efficiency as the competing methods.